Biodiversidade e variação espaço-temporal da abundância das populações de camarões e estrutura populacional de Farfantepenaeus subtilis (Pérez-Farfante, 1967) (Penaeidae) em um estuário do litoral amazônico brasileiro - FERREIRA, Valdimere (Universidade Federal do Pará, 2014)
This study investigated the biodiversity and spatial-temporal distribution of abundance of populations of shrimp and described the population structure of the Farfantepenaeus subtilis in an Amazonian Estuary. The shrimps were collected monthly from August 2006 to July 2007 in the rainy (January to June) and dry (July to December) season with bottom trawling and beach seine in the Middle-Upper (MU), Medium (M) and Low (L) sectors. In each sector two sites were sampled, of which two bottom trawling five minutes each and three beach seine of 150 m2 each were performed. The variables: temperature, pH and salinity of water and grain size and organic matter of the sediment were analyzed. For each shrimp were recorded the length Total - CT and cephalothorax - CC, total weight, sex and stage of gonadal maturation. The salinity differ between sectors I and MS (p <0.05) and M showed low organic matter content. The salinity differ significantly among sectors I and MS (p <0.05) and M showed low organic matter content. In all sectors the sand grains were prevalent on substrate, especially the fine sand in sector M. A total of 11,939 shrimps were collected, divided into twelve species and six families. Palaemonidae and Penaeidae had higher richness with five and three species, respectively. Penaeidae, Sergestidae and Palaemonidae had higher abundance, with Xiphopenaeus kroyeri, F. subtilis, Acetes marinus and Nematopalaemon schmitti, contributing 43, 31, 21 and 1.3% of the total catch, respectively. The species F. subtilis, X. kroyeri and Litopenaeus schmitti contributed 97% of the total biomass. The density and biomass from F. subtilis differ between the rainy and dry seasons (p <0.05) being higher in rainy season. In the rainy season, the density of X. kroyeri was higher in sectors M and I and dry season in sectors MS and M with higher biomass in sector I in both seasons. The density and biomass A. marinus was high in sector I (p <0.05). The salinity, sand, silt and clay significantly influenced the spatial and temporal distribution of abundance of shrimps (p <0.05). The CC of female F. subtilis was higher than males with 13.7 mm and 12.8 mm, respectively and differed in March (p <0.05). Females were more abundant and sex ratio was 0.8:1 especially in January, February, May and the total analysis (p <0.05). Developed shrimps occurred in rainy and abundance of juveniles was higher from January to June when it occurs the most intense peak spawning in the open sea.